Viljeltyjen turve- ja multamaiden pinta-ala ja alueellinen jakauma Suomessa - Myllys, Merja; Sinkkonen, Marko (Suoseura, 2004)
The area and distribution of cultivated organic soils in Finland Suo 55(3-4): 53-60
The area and distribution of cultivated organic soils in Finland
Keywords: Ma; Ka; viljelymaa; peltoala; turvemaat; multamaat; eloperäiset maat; soil; peat soils; humus; organic soils; peatland; mire cultivation; arable area